'Big needles, small bodies'—the absence of acupuncture treatment for infants in contemporary Shanghai: a qualitative study. Issue 11 (9th November 2015) - Skjeie, Holgeir; Brekke, Mette
Abstract : Objective: To explore contemporary practices and clinical recommendations regarding the use of acupuncture for infants by Traditional Chinese Medicine (TCM) practitioners in Shanghai. Design: A qualitative study consisting of four field visits between February 2014 and March 2015. Data was collected using participant observation, focus group interview, in-depth interview, textbook page analysis and informant validation. Participants: 14 Shanghainese professionals, including interpreters and TCM practitioners, of which seven were acupuncturists. Setting: The Longhua Hospital (paediatric, acupuncture and Tui na departments) in southern Shanghai and the campus of the Shanghai University of Traditional Chinese Medicine. Results: The Longhua Hospital outpatient acupuncture clinic receives 400 consultations on average per day. Children, including patients from the paediatric department, are referred to this clinic. During 3 days of participant observations at this department, we saw two children. No infants. During 3 days at the paediatric department and 1 day at the Tui na department we saw no referrals. Formal interviews and informal conversations with acupuncturists and other TCM professionals revealed that acupuncture was neither routinely practiced nor recommended for infants and small children. Acupuncture was considered potentially painful for this young patient population. Alternative treatment options such as herbal treatments or medical massage were widely available and preferred. Western medical diagnostics and treatment were also used, recommended, and trusted. Conclusions: Acupuncture for infants is not a preferred therapeutic method among TCM practitioners working in contemporary Shanghai. Acupuncture on broad indications in infants appears to be a Western practice with little basis in TCM modern-day practice.